Circular economy assessment tool for end of life product recovery strategies - Yohannes A. Alamerew; Daniel Brissaud (Journal of Remanufacturing, 2019)
Circular Economy (CE) aims to maintain the value of products, components, materials, and resources in the economy for as long as possible. Current end of life (EoL) product circularity decision-making methods are focused on technical and economic factors neglecting other crucial areas such as legislative pressure and customer demand, which are pertinent in the decision-making process. This paper presents a decision-making method to evaluate end of life product circularity alternatives at strategic level. A Product Recovery Multi-Criteria Decision Tool (PR-MCDT) is proposed to evaluate product circularity strategies from an integrated point of view, i.e. by simultaneously taking into account technical, economic, environmental, business, and societal aspects. The paper also identifies key end of life decision-making factors to assess product recovery strategies. An illustrative example is presented and discussed to show the applicability of the tool for the selection of product recovery options. A PR-MCDT is used at the senior/middle management level to ensure strategic decisions, which then promote success of the company.
Keywords: 650; Circular economy; Remanufacturing; End of life strategy; Product recovery; Multicriteria decision methodology